ON THE “SCIENTIFICITY” OF MICROECONOMICS: INDIVIDUAL DEMAND, AND EXCHANGE-VALUE DETERMINATION - DOMINIQUE, C-René (Theoretical and Practical Research in Economic Fields, 2017)
This note examines how the concept of utility has led neo-classical economists astray. It first briefly reviews the thoughts of the early pioneers who have engaged these economists on the utility trail. It next scrutinizes the requirements imposed on the preference set of the consumer in view of extracting a utility function having anticipative properties. Then it shows how set theory can solve the dynamic exchange process and value determination without any need for a utility function.